A new fluorescent probe based on BODIPY for testing NO2 released from propellants - Ying-cui Cui; De-bin Xia; Zhong-yu Cui; Yu-jing Li; Jian Zhang; Ping Wang; Ting Guo; Kai-feng Lin; Yu-lin Yang (Energetic Materials Frontiers)
After long-term storage, solid propellants often exhibit various aging characteristics. This study presents a strategy for assessing the state of propellants using the Boron-dipyrrole Ni complex (BDP-Ni) as a probe. The thermogravimetric and cyclic voltammetry results indicate that the probe BDP-Ni exhibits excellent thermal stability and electrochemical stability. By utilizing both solution and thin films of BDP-Ni, we successfully detected NO2 gas and observed a significant fluorescence intensity response to varying concentrations of NO2. Subsequently, selectivity experiments with other characteristic gases confirmed the high specificity of BDP-Ni for NO2. Furthermore, accelerated aging experiments of propellants were conducted alongside BDP-Ni films under identical conditions. This method can not only calculate the NO2 gas concentration released from propellants based on fluorescence changes of BDP-Ni but also infer the state of propellants. The probe can additionally function as an 'alarm' to evaluate the extent of stabilizer consumption in the propellant. This work illustrates the preparation of the fluorescence probe and offers a new approach for detecting characteristic gases released from propellants.